Muscat and the Portuguese: economic and political dynamics in the early 16th century (1507-1529) - Dejanirah Couto (Arabian Humanities, 2022)
Based on recently published literature, this article examines the relationship between Oman’s coastal towns and the Portuguese in the early decades of the 16th century. He takes as an example the port of Muscat, whose remarkable natural conditions had favored, from medieval times, its supremacy as a bridgehead for the hinterland regions and leader of the commercial networks of the West Indian Ocean, to the detriment of other Omani ports. This superiority, which also rest on its ability to orient its economy on several fronts, was reinforced by the presence of the Portuguese, who, following their attack in 1507, appointed Muscat as a stopover of their fleets and established there a factory. In addition, the progressive involvement of the Portuguese in the economic life of Muscat was accompanied by a growing political interference in the internal affairs of the city, symbolized by an implication in the conflicts which opposed the urban elites of Muscat to those of the other cities of Oman and also to Hormuz, which, while exercising its authority over the towns on the Omani side, had become, after the double conquest of Afonso de Albuquerque (1507 and 1515), protectorate of the Portuguese.